Deepfake Porn And Victim Protection: Legal Challenges In The Era Of Technological Disruption Within The Framework Of The SDGs - Yanti, Evi; Susanti, Heni (Proceeding International Conference on Social Sciences, 2026)
The development of generative artificial intelligence technology has given birth to the phenomenon of deepfake porn that allows the creation of synthetic sexual content with a high resemblance to identity without the consent of the represented subject. This phenomenon creates a crisis of authenticity to the identity and self-representation of victims and presents new challenges for the legal protection system. This study aims to analyze deepfake porn as a form of technological disruption that has an epistemic and ontological impact, evaluate the form of legal protection for victims within the framework of Indonesian laws and regulations, and formulate the need for norm reformulation based on the principles of the Sustainable Development Goals (SDGs). The research method used is normative legal research with conceptual, legislative, and philosophical approaches to knowledge, through an analysis of the Sexual Violence Crime Law and regulations related to the digital space. The results of the study show that deepfake porn is not only a violation of digital law, but also a visual truth crisis that undermines the integrity of the victim's identity. The existing legal framework has provided a basis for protection, but it still contains normative gaps related to the synthetic character of content and the responsibilities of the technology ecosystem. The reformulation of norms is necessary through explicit recognition of digital sexual manipulation, rapid removal mechanisms, victim recovery, and expanded platform liability. In the discussion, the protection of victims of deepfake porn is placed within the framework of the SDGs, especially the goals of gender equality and strengthening justice and effective institutions, so that legal protection is positioned as part of the development of digital justice that is oriented towards human dignity.